2018
DOI: 10.1021/acs.macromol.8b00809
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Crystallization and Entanglements in the Amorphous Phase of the Crystal-Fixed Polymer Poly(ϵ-caprolactone)

Abstract: This work focuses on the influence of amorphous-phase entanglements on the semicrystalline morphology of poly­(ϵ-caprolactone). This polyester is classified as crystal-fixed; i.e., it displays no translational chain dynamics in the crystals. We study a wide range of well-entangled samples with molecular weights up to several million using polarization microscopy to assess the lamellar growth rate, small-angle X-ray scattering and proton time-domain NMR to characterize the morphology, and proton multiple-quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 67 publications
5
62
0
Order By: Relevance
“…Wang et al characterized the entanglement state of iPP by rheological testing, and then studied the crystallization behavior of iPP-disentangled melt [ 35 ]. R. Kurz et al also related the entanglement in the melt to the entanglement in the amorphous zone; their experimental results suggest that entanglement controls the thickness of the amorphous zone [ 36 ]. Recently, Men et al revealed the decisive role of entanglements in the transition between the α and tetragonal crystal form of Polybutene-1 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al characterized the entanglement state of iPP by rheological testing, and then studied the crystallization behavior of iPP-disentangled melt [ 35 ]. R. Kurz et al also related the entanglement in the melt to the entanglement in the amorphous zone; their experimental results suggest that entanglement controls the thickness of the amorphous zone [ 36 ]. Recently, Men et al revealed the decisive role of entanglements in the transition between the α and tetragonal crystal form of Polybutene-1 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the melt viscosity is considered to be highly related to the molecular weight of a polymer due to the chain entanglements. 48,49 In our case, the molecular weight level of all coPA6 was close, indicating that the difference in melt viscosity was highly dependent on material characteristics. 50 However, the high melt viscosity in PA6 B1 and PA6 B2 indicated that the trace-content BAHT-AA loading in the PA6 backbone can enhance the intermolecular interaction by π-π stacking of the aromatic ring.…”
Section: Tensile Properties and Water Absorptionmentioning
confidence: 49%
“…In a model suggested by Men and coworkers, a semicrystalline polymer is considered as a composite of two interpenetrating networks between interconnected lamellae blocks and the entangled amorphous network . The critical aspects of the true stress‐strain curves of such polymers include, local intralamellar slip processes just before yield and after a purely elastic deformation (point A), and a change into a collective activity of slip motions all over the lamellae at the yield point of the polymer (point B). On further strain, lamellae disaggregation and chain unfolding (also referred to as mechanical melting) and recrystallization into fibrillar structures occur (point C) .…”
Section: Resultsmentioning
confidence: 99%